2010
DOI: 10.1095/biolreprod.110.086546
|View full text |Cite
|
Sign up to set email alerts
|

Release of Free and Conjugated Forms of the Putative Pheromonal Steroid 11-Oxo-etiocholanolone by Reproductively Mature Male Round Goby (Neogobius melanostomus Pallas, 1814)

Abstract: Previous studies of the round goby (Neogobius melanostomus Pallas, 1814), an invasive fish species in the Laurentian Great Lakes of North America, have shown that this species has the ability to both synthesize and smell steroids that have a 5 beta-reduced and 3 alpha-hydroxyl (5 beta,3 alpha) configuration. An enzyme-linked immunoassay (EIA) for 3 alpha-hydroxy-5 beta-androstane-11,17-dione (11-O-ETIO) has been used to show a substantial rise in the rate of release of immunoreactive compounds into the water w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…A similar observation was made of African catfish (Clarias gariepinus) males, where the most potent testicular odorant was found to be 20one-P-3-G (Lambert and Resink, 1991). Androstanes and pregnanes with a 5β,3α configuration are also potent odorants for the round goby (Neogobius melanostomus, Pallas 1814) (Murphy et al, 2001), and recent studies have demonstrated that round goby males release several conjugated forms of these steroids via their urine (Katare et al, 2011), eventually to attract females (Tierney et al, 2013). However, in the round goby, the olfactory receptors detecting ETIO-3-G appear to be less specific than those in tilapia; several unconjugated androstanes, pregnanes and even androsten, are detected by the same (ETIO-3-G) receptor site (Murphy et al, 2001).…”
Section: Binary Mixture Testssupporting
confidence: 60%
“…A similar observation was made of African catfish (Clarias gariepinus) males, where the most potent testicular odorant was found to be 20one-P-3-G (Lambert and Resink, 1991). Androstanes and pregnanes with a 5β,3α configuration are also potent odorants for the round goby (Neogobius melanostomus, Pallas 1814) (Murphy et al, 2001), and recent studies have demonstrated that round goby males release several conjugated forms of these steroids via their urine (Katare et al, 2011), eventually to attract females (Tierney et al, 2013). However, in the round goby, the olfactory receptors detecting ETIO-3-G appear to be less specific than those in tilapia; several unconjugated androstanes, pregnanes and even androsten, are detected by the same (ETIO-3-G) receptor site (Murphy et al, 2001).…”
Section: Binary Mixture Testssupporting
confidence: 60%
“…The procedure for generating methanol extracts of water that held reproductive males (RM) has been described elsewhere (Katare et al, 2011). Each RM (chosen on the basis of secondary sexual characters; Belanger et al 2004) was isolated in 1 l of dechlorinated water, which was collected after 4 h ("pre-injection").…”
Section: Generation Of Methanol Extracted Male Watermentioning
confidence: 99%
“…Individual stocks were diluted 100× further in dechlorinated water for EOG testing; thus, tested concentrations of extracted compounds were all below the original concentrations produced by the RMs. We used a custom immunoassay to measure the amount of released immunoreactive unconjugated and conjugated 11-O-ETIO in the methanol extracts (Katare et al, 2011). The release rate of immunoreactive 11-O-ETIO was 2.13±0.64 ng/ml/h in methanol extracts prepared prior to injection.…”
Section: Generation Of Methanol Extracted Male Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, steroids were identified as pheromones and adversely affect fish behavior even at extremely low concentrations (Kolodziej et al, 2003). For example, androgens at picomolar concentrations elicit both odorant and pheromonal responses in fish (Adams et al, 1987;Moore and Scott, 1991;Serrano et al, 2008;Katare et al, 2011).…”
Section: Introductionmentioning
confidence: 99%